Engaging in the 'course efficiency' discussion: national drivers and local responses. Issue 8 (14th September 2019) - Walls, Justin; Carr, Andrea; Kelder, Jo-Anne; Ennever, Ellen
Abstract: This article presents a method to evaluate undergraduate and postgraduate course teaching efficiency systematically, alongside measuring effectiveness of curriculum content and delivery. We argue that efficiency is aligned to cost and revenue while effectiveness is a quality-related construct. These potentially antagonistic elements – cost, revenue and quality – must be kept in balance if courses are to be attractive to students (high quality) and financially viable. Curriculum data collection and analysis spanned micro (unit), meso (course) and macro (faculty) level. Revenue data consisted of annual teaching student enrolment numbers by unit of study, aggregated to course level. Cost data included academic and administrative staff costs, and student professional experience placement expenditure. A teaching revenue to cost of delivery ratio metric and course quality score metric were developed to enable comparisons of units and course performance. Over time, these metrics, when utilised together, could be used to determine the impact of quality improvement interventions on teaching cost and revenue and vice versa. We argue that this approach supports strategic planning and actions to improve both efficiency and effectiveness of units and courses, without negatively affecting quality.